Fabrication of halide-perovskite resonant microcylinders by nanoimprint lithography. (March 2020) - Polushkin, A S; Kruk, S; Malurean, R; Tiguntseva, E Yu; Zakhidov, A; Bogdanov, A A; Kivshar, Y; Makarov, S V
Abstract: Halide perovskites are promising materials for optoelectronic devices, solar cells and various photonic applications due to their unique optical and electronic properties and low-cost fabrication. Halide perovskites micro and nanoscale structures have demonstrated high resonance properties last decade. Moreover, these materials allow high throughput creation of advanced nanophotonic designs employing nanoimprint lithography. Here, we develop this fabrication approach to create halide perovskites resonant microcylinders. Our study of the obtained microobjects demonstrates that the nanoimprint lithography yields desirable size and shape, as well as preserved photoluminescent properties of the microcylinders.